The Role of Emotional Intelligence in Entrepreneurs' Perceptions of Success: An Exploratory Study - Zhou, Haibo; Bojica, Ana Maria (Senate Hall, 2017)
This study contributes to the entrepreneurship literature by introducing emotional intelligence (EI) as an additional factor that explains how entrepreneurs perceive their own success. Using survey data from a sample of Dutch entrepreneurs, we find that emotionally intelligent entrepreneurs are more likely to judge positively their entrepreneurial success in terms of: employee satisfaction, social responsibility, personal satisfaction, customer satisfaction and business performance. Furthermore, not all EI dimensions are equally relevant to explain self-perceived success. In this respect, we find that the (self-perceived) ability to regulate emotions of other people is most strongly linked to entrepreneurial success. Keywords: Emotional intelligence, regulate emotions of other people, (self-perceived) success criteria, entrepreneurial success, Dutch entrepreneurs
Keywords: emotional intelligence|regulate emotions of other people|(self-perceived) success criteria|entrepreneurial success|Dutch entrepreneurs